Population pharmacokinetics, dosing optimization and clinical outcomes of biapenem in patients with sepsis - Chen, Dayu; Wu, Xuanyu; Zhang, Haixia; Yao, Huimin; Jin, Lu; Luo, Xuemei; Liu, Jinchun; Wu, Zejun; Li, Yuanchen; Xu, Wei; Ge, Weihong; Chen, Xingkai; et al. (Frontiers in Pharmacology, 2024)
Biapenem is a carbapenem antibiotic widely used in Asia, can be used for the treatment of adults and children with infections due to susceptible bacteria. Although biapenem is utilized in the treatment of a diverse range of bacterial infections, current pharmacokinetic data in the context of septic populations remain limited. Consequently, our research aims to evaluate the pharmacokinetics and efficacy of biapenem within a septic population to optimize biapenem therapy. In this study, we characterized the pharmacokinetics of biapenem in septic patients using a population pharmacokinetic (PPK) approach. The clinical PK data to develop the PPK model were obtained from 317 septic patients admitted to Nanjing Drum Tower Hospital between 2018 and 2022. All patients were randomized to the modeling and validation cohorts at a 3:1 ratio, with PPK modeling and validation performed utilizing the NONMEM software. The model found to best describe the available data was a two-compartment PPK model with first-order elimination characterized by the parameters clearance (CL), central volume (V1), peripheral volume (V2), and intercompartmental clearance (Q). A covariate analysis identified that creatinine clearance (CLCR) was a significant covariate influencing biapenem CL, while blood urea nitrogen (BUN) was a significant covariate influencing biapenem Q. Accoding to the clinical outcome analyses, 70% of the time that the free antimicrobial drug concentration exceeds the MIC (fT>MIC) is associated with favourable clinical 2 outcomes. The PPK model was then used to perform Monte Carlo simulations to evaluate the probability of attaining 70% fT>MIC. A final PPK model of biapenem was established for patients with sepsis. The current daily dosage regimen of 1.2g may insufficient to achieve 70% fT>MIC in septic patients. The dosage regimen of 600mg every 6 hours appears to be the optimal choice.